Minimum Wage and its Reflections in Administrative Thinking - Kutbi, Lina; Alroujaye, Lamees Saleh Ali (The Arab Journal of Administration, 2025)
This research examines the historical evolution of the concept of minimum wage, with a focus on the policies implemented to determine it. These policies were intended to contribute to achieving social justice and improving the living standards of workers, as well as promoting economic growth and sustainable development in various countries around the world. However, such policies remain inadequate and, in many cases, below the required level. This inadequacy leads to a disruption in the relationship between the wages paid and the actual living costs and human needs of workers. This imbalance negatively impacts economic development and the social structure of societies, deepening the gap between wages and essential needs, which further exacerbates social and economic inequality. To address these challenges, the research highlights the necessity of formulating a new wage and incentive system based on the principles of Islamic administrative thought. This approach is seen as a tool to achieve a fair balance between wages and workers’ needs, thus contributing to the improvement of economic and social conditions. The study employs a descriptive-analytical methodology to explore the subject, reviewing the concept of the minimum wage and its development across various historical periods, in addition to the theories and models that have influenced its policies. The research also discusses the positive and negative impacts of implementing minimum wage policies on social justice. Furthermore, it offers practical recommendations and proposals for developing a wage and incentive system that aligns with the principles of Arab-Islamic administrative thought, ensuring sustainable economic and social development over the long term.